The place of dopamine in the cortico-basal ganglia circuit - HABER, SUZANNE N. (Neuroscience, 2014)
The midbrain dopamine neurons play a central role developing appropriate goal-directed behaviors, including the motivation and cognition to develop appropriate actions to obtain a specific outcome. Indeed, subpopulations of DA neurons have been associated with these different functions: the mesolimbic, mesocortical, and nigrostriatal pathways. The mesolimbic and nigrostriatal pathways are an integral part of the basal ganglia through its reciprocal connections to the ventral and dorsal striatum respectively. This chapter reviews the connections of the midbrain dopamine cells and their role in integrating information across limbic, cognitive and motor functions. Emphasis is placed on the interface between these functional domains within the striatum through corticostriatal connections, through the striato-nigro-striatal connection, and through the lateral habenula projection to the midbrain.